A review on computational fluid dynamic simulation for rotating packed beds. Issue 4 (26th December 2018) - Yang, Yu‐Cheng; Ouyang, Yi; Zhang, Na; Yu, Qing‐Jie; Arowo, Moses
Abstract: A rotating packed bed (RPB) is one of the cutting‐edge process intensification technologies due to its high mass transfer and mixing efficiency. Nevertheless, owing to the complex structure and hydrodynamic characteristics of RPBs, valuable data inside the reactor is hard to obtain by conventional experimental methods. Computational fluid dynamics (CFD) owing to its unique advantages of low cost, completeness of data and ability to simulate real and ideal conditions, has been adopted by many researchers to carry out fundamental research and practical application of RPBs in recent years. This paper therefore elaborates on the research progress on CFD simulation of RPBs. The building of a physical model of these reactors as well as selection of mathematical models are described, then applicability and accuracy of these models are compared and discussed. Simulation results for gas and multiphase flow in reactors are also presented. Additionally, the application of CFD to mixing and mass transfer between phases and processes in rotating packed beds is introduced. Optimum designs of reactors by the CFD method are also described. Finally, problems remaining with CFD simulation of rotating packed beds and future development directions are discussed. © 2018 Society of Chemical Industry